2019
DOI: 10.3390/met9101126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2024 Al Alloy Insert on the Grain Refinement of a 2024 Al Alloy Prepared via Insert Mold Casting

Abstract: In this study, an insert mold casting was fabricated by inserting 2024 Al extruded rods into a 2024 Al melt. The molds were kept at a 2024 Al melt for different times. The 2024 Al extruded rods were used to refine the 2024 Al alloy grains because the advantage of this method is that it is contamination free compared with other grain refiners. Moreover, we investigated the macro and microstructure of the ingots. Further, we analyzed the refinement mechanism of the 2024 Al rod on the 2024 Al alloy. Our result sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…However, the purpose of that method is to obtain an excellent metallurgical bonding between the insert and the melt. Our previous study found that inserting a cold 2024 Al alloy rod into the 2024 Al melt during mold casting can refine the grains [17] . Eskin et al [18] confirmed the grain refinement effect of introduction the same-alloy rod into the melt in a standard TP-1 mold casting and achieved significant grain refinement.…”
Section: Structures and Macrosegregation Of A 2024 Aluminum Alloy Fabricated By Direct Chill Casting With Double Cooling Fieldmentioning
confidence: 99%
“…However, the purpose of that method is to obtain an excellent metallurgical bonding between the insert and the melt. Our previous study found that inserting a cold 2024 Al alloy rod into the 2024 Al melt during mold casting can refine the grains [17] . Eskin et al [18] confirmed the grain refinement effect of introduction the same-alloy rod into the melt in a standard TP-1 mold casting and achieved significant grain refinement.…”
Section: Structures and Macrosegregation Of A 2024 Aluminum Alloy Fabricated By Direct Chill Casting With Double Cooling Fieldmentioning
confidence: 99%
“…Although these measures can accelerate the utilization of TiO 2 to visible light, it is an urgent problem to solve the free charge recombination caused by light excitation in a single semiconductor. Extensive research has demonstrated the preparation of two types of semiconductors with wide and narrow band gaps to fabricate heterostructure materials, which exhibit superior photocatalytic activity compared to individual catalytic materials [22][23][24]. Consequently, TiO 2 generally construct heterojunctions with other narrow band gap semiconductors that align with its band positions, which can transfer the light response rang from the ultraviolet region to the visible region.…”
Section: Introductionmentioning
confidence: 99%